En renässans för kallväxthuset - Henriksson, Yvonne (2007)
The unheated greenhouse was originally a development from orangeries in the 1700th century and in 1930 and 1940 in blocks of greenhouses in the province of Scania. Today unheated greenhouses are used in permaculture, in the"eco villages" and in commercial culturing. Of the total Swedish commercial greenhouse area is today 8 % used as unheated greenhouses (SJV). This essay is based on the acceptance that unheated greenhouses will have a renaissance as production units. In the light of the today's debate about energy – and environment and the condition concerning this, the unheated greenhouse becomes an alternative. The purpose of this essay is to make an arguing synopsis about unheated greenhouses for using in acting as teacher, consultant and inspirer and also for taking part of the acceptance as "for" or "against". The information is based on literature studies and information gathered with the keywords unheated greenhouse, coolhouse, coldhouse, greenhouse, type of greenhouse, orangery, greenhouse cultur, swedish greenhouse culture and permaculture, data gathering through SCB/SJV and by interviews with persons in the garden branch. My conclusion is that the unheated greenhouse could have a renaissance as a production unit. In this context it is important to give cultivators of greenhouses with experiences of unheated greenhouses great possibilities to share their knowledge, and through education possibility to change attitudes concerning unheated greenhouses.